Comparative study of the ovarian morphology in the order Polydesmida (Diplopoda) and description of unusual structures in the female reproductive system - Pinheiro, T. G. [UNESP]; Marques, M. I.; Fontanetti, C. S. [UNESP] (FapUNIFESP (SciELO), 2013)
Polydesmida is the largest order in the class Diplopoda in terms of the number of species, genera and families, but there are few studies of the ovarian morphology of species in this order. This study aimed to perform a comparative study of the ovarian morphology of three species from this order to increase the understanding of the morphological evolution of this system in Polydesmida. Adults females of two of these species, Poratia salvator and Myrmecodesmus hastatus, belonging to the family Pyrgodesmidae, had a unpaired ovary that formed a tubular organ containing oocytes, with P. salvator present grouping of oocytes into a structure similar to ovisacs. This condition appeared to be apomorphic and was associated with the small size of these species (< 10 mm) and their short life cycle. The third species, Telonychopus klossae (Chelodesmidae), had a large body and an ovary with paired ovisacs, which was symplesiomorphic with other Polydesmida families.
Estudo comparativo da morfologia ovariana na ordem Polydesmida (Diplopoda) e descrição de estruturas incomuns do sistema reprodutor feminino
Keywords: Apomorphy; Millipedes; Reproduction; Synapomorphy